Estimating and Projecting Efficacy of Monoclonal Antibodies Against Respiratory Syncytial Virus Beyond Clinical Trial Periods - Dawei Wang; John C. Lang; Klodeta Kura; Yao-Hsuan Chen (Vaccines, 2026)
Background: Clinical trials of respiratory syncytial virus (RSV) monoclonal antibodies (mAbs) have followed participants for up to 180 days, covering a typical single RSV season. However, to assess the full clinical impact of mAb administration, post-trial efficacy estimates are needed, particularly in countries where RSV circulation extends beyond six months. Methods: In this study, we applied a previously published Bayesian framework to estimate how the level of protective efficacy against RSV provided by clesrovimab and nirsevimab changes over the first year after administration. Using this Bayesian framework, which modeled new infections as Poisson processes with a Gaussian process prior for the force of infection and a parametric waning function for the intervention arm, we estimated placebo incidence rates and posterior waning functions. We validated our estimates by calculating model-estimated cumulative trial-period efficacy using an Incidence Rate Ratio (IRR) approach and by reconstructing event-free probability curves, comparing both with published clinical trial results. Results: Model-derived cumulative efficacy estimates closely matched trial-reported results for both products. The model-projected instantaneous probability of being protected at one year—an extrapolation beyond the observed trial follow-up—was 24.6% (95% CrI: 1.6–57.0%) for clesrovimab and 12.8% (95% CrI: 1.2–44.4%) for nirsevimab, with substantially overlapping credible intervals. Conclusions: Both RSV mAbs were projected to provide some level of protection throughout the first year following administration, with broadly similar levels of protection.